2022
DOI: 10.48550/arxiv.2205.13217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superposition of causal order in quantum walks: non-Markovianity and causal asymmetry

Abstract: We set the criteria for a quantum walk to exhibit nontrivial dynamics when placed in an indefinite causal order and study two-period quantum walks when the evolution operator is arranged in a causally ordered sequence and in an indefinite causal order using quantum switch. When either forward or backward causal sequence is implemented, one observes a causal asymmetry in the dynamics, in the sense that the reduced dynamics of the coin state is more non-Markovian for one particular temporal order of operations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It was also shown in Ref. [44] that in quantum random walks where the dynamics of the reduced coin state is non-Markovian [45], by placing the walk's evolution operators in an indefinite causal order, there is an increase in non-Markovianity as compared to a fixed causal order. Even more recently, it was shown that for channels that are non-Markovian but do not offer backflow of information, known as eternally non-Markovian channels [46], such that its non-Markovianity is "hidden," placing these channels in the quantum switch setup can activate this hidden non-Markovianity to allow backflow of information [47].…”
Section: Introductionmentioning
confidence: 94%
“…It was also shown in Ref. [44] that in quantum random walks where the dynamics of the reduced coin state is non-Markovian [45], by placing the walk's evolution operators in an indefinite causal order, there is an increase in non-Markovianity as compared to a fixed causal order. Even more recently, it was shown that for channels that are non-Markovian but do not offer backflow of information, known as eternally non-Markovian channels [46], such that its non-Markovianity is "hidden," placing these channels in the quantum switch setup can activate this hidden non-Markovianity to allow backflow of information [47].…”
Section: Introductionmentioning
confidence: 94%
“…We suggest that the quantum switch's advantages has nonnegligible contributions from non-Markovian effects. As far as we are aware, despite some works discussing non-Markovianity and indefinite causal order together [22][23][24][25], we are the first to make this connection and proposal 1 .…”
Section: Background: Quantum Compositions Of Channelsmentioning
confidence: 95%
“…For example, it was shown in Ref. [23] that in quantum random walks where the dynamics of the reduced coin state are non-Markovian [24], by placing the walk's evolution operators in an indefinite causal order, there is an increase in non-Markovianity as compared to a fixed causal order. It was also shown that for channels that are non-Markovian but do not offer backflow of information, e.g., eternally non-Markovian channels [76], such that its non-Markovianity is "hidden", placing these channels in the quantum switch setup can activate this hidden non-Markovianity to allow backflow of information [25].…”
Section: Channel Compositions With Non-markovianitymentioning
confidence: 99%